Rain forest fragmentation and the structure of Amazonian liana communities - Laurance, William F. (Ecology, 2020)
In tropical forests, lianas (woody vines) are important structural parasites of trees. We assessed the effects of forest fragmentation, treefall disturbance, soils, and stand attributes on liana communities in central Amazonian rain forests. Over 27 500 liana stems (≥2 cm diameter at breast height [dbh]) were recorded in 27 1-ha plots in continuous forest and 42 plots in 10 forest fragments ranging from 1 to 100 ha in area. For each plot, an index of forest disturbance was determined from a 20-yr study of tree-community dynamics, and 19 soil-texture and chemistry parameters were derived from soil surface samples (top 20 cm). Liana abundance was 187-701 stems/ha, and liana aboveground dry biomass varied from 3.7 to 12.3 Mg/ha. Liana abundance increased significantly near forest edges and was significantly positively associated with forest disturbance and significantly negatively associated with tree biomass. Liana biomass was similarly associated with disturbance and tree biomass but also increased significantly along soil-fertility gradients. Plots near forest edges had a significantly higher proportion of small (2-3 cm dbh) lianas and relatively fewer large (≥4 cm dbh) lianas than did sites in forest interiors. Liana communities were further assessed by comparing their species richness, composition, climbing guilds, and frequency of tree infestation in three 10-ha fragments. Within each fragment, data were collected in 24 small (400-m2) plots, with half of the plots near edges and half in interiors. Significantly more trees were infested on fragment edges than in interiors. All three major guilds (branch-twiners, mainstem-twiners, tendril-twiners) were significantly more abundant on edges. Species diversity of lianas (as measured by Fisher's diversity index) also was significantly higher on edges, and this was not simply an artifact of increased liana abundance on edges. We conclude that many aspects of liana community structure are affected by habitat fragmentation, and we suggest that lianas can have important impacts on forest dynamics and functioning in fragmented rain forests. By creating physical stresses on trees and competing for light and nutrients, heavy liana infestations appear partly responsible for the dramatically elevated rates of tree mortality and damage observed near fragment edges.